Da análise econômica do direito à análise jurídica da economia: o paradigma das decisões judiciais sob o olhar do direito ao desenvolvimento - Soratto, Fernanda Peres (Universidade do Vale do Rio dos Sinos, 2022)
This doctoral thesis aims to examine the Theory of Judicial Decision, under the paradigm of Economic Analysis of Law, and the use of Legal Economic Analysis (AED) with a view to achieving the right to development. From this angle, the research problem considers, in the context of contemporaneity, what is the possibility of an inversion in the use of the postulates of the Economic Analysis of Law for a Legal Analysis of the Economy as the foundation of the judicial decision and with the purpose of contributing to the law to development? Therefore, the qualitative methodological strategy is established in the fundamental premises of the AED, as tools for rethinking a rationalist proposal on how judges should justify court decisions in order to realize the right to development. From this perspective, the hypotheses for the foundation of the problem were synthetically established as follows: the first one, which involves a change in the paradigm of judicial decisions, beyond hermeneutics, where the judge must analyze among the possible decisions which is the most efficient; the second, which addresses the use of the AED, in its descriptive conception, to examine the behavior of economic agents, aiming at guaranteeing the dignity of the human person, and not at maximizing profits; another, which considers legal decisions as signs of disrespect for fundamental rights, when carried out without analyzing their social and economic consequences for society and not only for the parties involved, and a last one, which highlights a Theory of Judicial Decisions founded in rational and coherent criteria and not in the subjectivism and creativity of the judges, because that way it will be legitimized to build the right, with emphasis on the right to development. At the end, the premises of the research were confirmed and the development of a theoretical proposition of Legal Analysis of the Economy, rationally designed with a view to assuring the right to development, was achieved.
Keywords: Pragmatismo jurídico; Eficiência econômica; Liberdades emancipatórias; Sociedade complexa; Efetivação de direitos; Legal pragmatismo; Economic efficiency; Emancipatory freedoms; Complex society; Enforcement of rights; ACCNPQ::Ciências Sociais Aplicadas::Direito